# Show that</

A = A2 = = Now, A2 – 3A – 7 = 0

= = = So, A2 – 3A – 7I = 0

Multiply by A – 1 both sides

= A.A. A – 1 – 3A. A – 1 – 7I. A – 1 = 0

= A – 3I – 7A – 1 = 0

= 7A – 1 = A – 3I

= A – 1 = Hence, A – 1 = Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

If <span lang="ENMathematics - Board Papers

Using matrices soMathematics - Board Papers

<span lang="EN-USMathematics - Board Papers

Using properties Mathematics - Board Papers

Using matrices, sMathematics - Board Papers

If A is square maMathematics - Exemplar

If <span lang="ENMathematics - Exemplar

The management coMathematics - Board Papers

If A is an invertMathematics - Board Papers

If <iMathematics - Board Papers